Effect Technology Information On Quality Financial Statement With Internal Control As Moderating Variable - Sarwono, Aris Eddy; Handayani, Asih (CV. Inara, 2021)
The problem with the low quality of financial reports in local governments is the reason this research was conducted. This research was conducted with the aim of analyzing the use of information technology on the quality of financial reports by considering the internal control system (SPI) factor. The location of this research is in the Karisidenan Surakarta area which includes 6 districts and 1 city. The population of this research is all state civil servants (ASN) in local governments who work in accounting. The sampling technique was using purposive sampling method. The results showed that the use of information technology had a positive effect on the quality of financial reporting in local governments, while the internal control system moderated the effect of the use of information technology on the quality of financial reporting in local governments.